How to: prophylactic interventions for prevention of Clostridioides difficile infection. (December 2021) - Reigadas, Elena; van Prehn, Joffrey; Falcone, Marco; Fitzpatrick, Fidelma; Vehreschild, Maria J.G.T.; Kuijper, Ed J.; Bouza, Emilio; ,
Abstract: Background: Clostridioides difficile infection (CDI) remains the leading cause of healthcare-associated diarrhoea, despite existing guidelines for infection control measures and antimicrobial stewardship. The high associated health and economic burden of CDI calls for novel strategies to prevent the development and spread of CDI in susceptible patients. Objectives: We aim to review CDI prophylactic treatment strategies and their implementation in clinical practice. Sources: We searched PubMed, Embase, Emcare, Web of Science, and the COCHRANE Library databases to identify prophylactic interventions aimed at prevention of CDI. The search was restricted to articles published in English since 2012. Content: A toxin-based vaccine candidate is currently being investigated in a phase III clinical trial. However, a recent attempt to develop a toxin-based vaccine has failed. Conventional probiotics have not yet proved to be an effective strategy for prevention of CDI. New promising microbiota-based interventions that bind and inactivate concomitantly administered antibiotics, such as ribaxamase and DAV-132, have been developed. Prophylaxis of CDI with C. difficile antibiotics should not be performed routinely and should be considered only for secondary prophylaxis in very selected patients who are at the highest imminent risk for recurrent CDI (R-CDI) after a thorough evaluation. Faecal microbiota transplantation (FMT) has proved to be a very effective treatment for patients with multiple recurrences. Bezlotoxumab provides protection against R-CDI, mainly in patients with primary episodes and a high risk of relapse. Implications: There are no proven effective, evidenced-based prophylaxis options for primary CDI. As for secondary prevention, FMT is considered the option of choice in patients with multiple recurrences. Bezlotoxumab can be added to standard treatment for patients at high risk for R-CDI. The most promising strategies are those aimed at reducing changes in intestinal microbiota and development of a new effective non-toxin-based vaccine.